2019
DOI: 10.2169/internalmedicine.1246-18
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Epstein-Barr Virus-positive (EBV+) Primary Central Nervous System Lymphoma (PCNSL) in a Patient with Clinical Features of Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids (CLIPPERS)

Abstract: Primary central nervous system lymphoma (PCNSL) and chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) can share clinical features and may be indistinguishable, even after brain biopsy. We encountered a case of Epstein-Barr virus-positive (EBV+) PCNSL recurrence in a patient with clinical features of CLIPPERS, and repeat brain biopsy was required to reach the correct diagnosis. Four years after the initial diagnosis and treatment of PCNSL, “peppering” punct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…In addition, mixed T- and B- lymphocytes infiltrated in the perivascular space and glial stroma. Not only our case, but also a few previous case studies have reported minimal inflammation and a mixture of T- and B-cells without demyelination [ 3 , 12 ]. Thus, T-cell dominant lymphocytic infiltration and demyelinating features are not mandatory characteristics of heralding inflammatory lesions.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, mixed T- and B- lymphocytes infiltrated in the perivascular space and glial stroma. Not only our case, but also a few previous case studies have reported minimal inflammation and a mixture of T- and B-cells without demyelination [ 3 , 12 ]. Thus, T-cell dominant lymphocytic infiltration and demyelinating features are not mandatory characteristics of heralding inflammatory lesions.…”
Section: Discussionsupporting
confidence: 69%
“…Nonetheless, the second histological analysis showed a mixed infiltration of T-and B-lymphocytes. Not only our case but also a few previous case studies have reported a mixture of T-and B-cells without demyelination [4,25]. Thus, the predominance of T-cell infiltration and demyelinating features are not mandatory characteristics of preceding inflammatory lesions.…”
Section: Discussionsupporting
confidence: 59%
“…Different hypotheses have been proposed regarding the relationship between lymphoma and CLIPPERS, which need further validation: (a) Lymphoma may be misdiagnosed as CLIPPERS at the onset or recurrence of symptoms. Studies reporting these cases highlight the role of biopsy and red flags such as inadequate response to corticosteroids in differentiating CLIPPERS from lymphoma 6–8,16 19 after a variable time in response to EBV reactivation, 11,20 chronic stimulation of perivascular antigens, 12 blood brain barrier dysregulation, 21 or compromised immune system resulting from treatment of CLIPPERS 9,10,12 ; (c) CLIPPERS may be a lymphocytic response through immune reconstitution or autoimmune reaction to various triggers such as HBV infection, influenza vaccination, or natalizumab withdrawal that may resolve or progress to more severe diseases such as lymphoma depending on management and other unknown prognostic factors 22,23 ; (d) CLIPPERS may be a spectrum rather than a disease caused by heterogeneous mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 To find previous lymphoma-associated cases up to November 2023, PubMed and Scopus online databases were searched using the keywords "CLIPPER" and "Lymphoma". To the best of our knowledge, 20 patients with lymphoma-associated CLIPPERS have been reported [6][7][8][9][10][11][12][13][14][15][16] since the first introduction of CLIPPERS. 2 A review of 10 patients by Zhang et al showed that patients with lymphoma-associated CLIPPERS had worse clinical outcomes and higher risk of mortality compared to those without lymphoma.…”
Section: Discussionmentioning
confidence: 99%